Urban expansion and forest reserves: Drivers of change and persistence on the coast of São Paulo State (Brazil) - Pierri Daunt, Ana Beatriz [UNESP]; Sanna Freire Silva, Thiago [UNESP]; Bürgi, Matthias; Hersperger, Anna M. (Elsevier, 2021)
Landscapes changes are a result of a wide range of interactions between actors and driving forces (DFs). In this study, we quantify the contribution of different types of DFs to processes of land change in the Northern Coast of São Paulo State (NCSP), Brazil, an important region for tourism and the energy sector. We analysed the relationship between DFs and the processes of land change from 1985 to 2000 and from 2000 to 2015 with partial least squares path modelling. The political and technological DFs were the most important groups of drivers for explaining the observed processes, especially the most dominant ones: policies on land use and environment (political DF), distances to the main transportation infrastructure (technological DF), and the presence of steep slopes in Serra do Mar (natural DF) influenced forest persistence and were also determinants for urban settlement distribution. The State Parks and the zones for nature conservation (political DF) were important for the maintenance of forest cover and overall the importance of political DF increased after 2000. In general, the DFs in NCSP were similar to those observed in other coastal and tourist regions, but surprisingly, despite a rapid population increase, demography did not explain urban and peri-urban growth. Urban growth was happening foremost in the zones for urban development and was accompanied by increases in water provision services and waste collection, whereas peri-urban sprawl was concentrated in conservation and agricultural zones, without investments in basic services. We conclude that an increasing demand for housing must be considered in future policies in NCSP, instead of solely focussing on economic interests in tourism and the energy sectors.
Keywords: Driving force; Environmental policy; Forest persistence; Land-use policy; Urban growth